Targeting Mitochondrial Protein Expression as a Future Approach for Cancer Therapy - Criscuolo, Daniela; Avolio, Rosario; Matassa, Danilo Swann; Esposito, Franca (Frontiers in Oncology, 2021)
Extensive metabolic remodeling is a fundamental feature of cancer cells. Although early reports attributed such remodeling to a loss of mitochondrial functions, it is now clear that mitochondria play central roles in cancer development and progression, from energy production to synthesis of macromolecules, from redox modulation to regulation of cell death. Biosynthetic pathways are also heavily affected by the metabolic rewiring, with protein synthesis dysregulation at the hearth of cellular transformation. Accumulating evidence in multiple organisms shows that the metabolic functions of mitochondria are tightly connected to protein synthesis, being assembly and activity of respiratory complexes highly dependent on de novo synthesis of their components. In turn, protein synthesis within the organelle is tightly connected with the cytosolic process. This implies an entire network of interactions and fine-tuned regulations that build up a completely under-estimated level of complexity. We are now only preliminarily beginning to reconstitute such regulatory level in human cells, and to perceive its role in diseases. Indeed, disruption or alterations of these connections trigger conditions of proteotoxic and energetic stress that could be potentially exploited for therapeutic purposes. In this review, we summarize the available literature on the coordinated regulation of mitochondrial and cytosolic mRNA translation, and their effects on the integrity of the mitochondrial proteome and functions. Finally, we highlight the potential held by this topic for future research directions and for the development of innovative therapeutic approaches.